Non-imaging microwave and millimetre-wave sensors for concealed object detection - Kapilevich, Boris Y.; Harmer, Stuart W.; Bowring, Nicholas J. (CRC Press, Taylor & Francis Group, 2015)
In response to the ever-increasing global threat of terrorist attacks, the personal screening industry has been growing at a rapid rate. Many methods have been developed for detecting concealed weapons and explosives on the human body. In this important new book, the authors discuss their experiences over the last decade designing and testing microwave and millimetre wave detection and screening systems. It includes examples of actual devices that they have built and tested, along with test results that were obtained in realistic scenarios.
Keywords: Scanning systems.; Metal detectors.; Explosives -- Detection.; Microwave detectors.; elektronické knihy; electronic books